2019
DOI: 10.3390/ijgi8120585
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Preliminary Damage Inspection by Classification of Terrestrial Laser Scanner Point Clouds through Systematic Threshold Definition

Abstract: This paper presents a novel approach for automatic, preliminary detection of damage in concrete structures using ground-based terrestrial laser scanners. The method is based on computation of defect-sensitive features such as the surface curvature, since the surface roughness changes strongly if an area is affected by damage. A robust version of principal component analysis (PCA) classification is proposed to distinguish between structural damage and outliers present in the laser scanning data. Numerical simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…A more sensitive detector provides more useful information to detecting wall surface changes. Many studies have shown that radiometric information of the point cloud can be effectively used to damage detection of buildings and structures [31,66].…”
Section: Discussionmentioning
confidence: 99%
“…A more sensitive detector provides more useful information to detecting wall surface changes. Many studies have shown that radiometric information of the point cloud can be effectively used to damage detection of buildings and structures [31,66].…”
Section: Discussionmentioning
confidence: 99%
“…for profile and areal features), a set of points is queried from within a defined 3D search radius of the pixel of interest. This optimal radius size has to be small enough to allow detection of the finest surface details, however, big enough to average out the effects of noise present in the datasets (Hadavandsiri et al 2019). The obtained subset of points is then used to determine the feature vector of that single point, and this procedure is repeated for all the points within each dataset.…”
Section: Surface Quality Assessmentmentioning
confidence: 99%
“…Moreover, Kazemian et al (2019) explored not only the nozzle distance from the surface but also the width of the layer that is extruded, thus adapting the process in a way to reach the desired outcome. Off-line concrete damage inspection using TLS and involving surface 3D feature computation is presented in Hadavandsiri et al (2019), and inspection using TLS intensity image classification in Zaczek-Peplinska and Osińska-Skotak (2018). According to the authors knowledge, the potential of geometric feedback systems is not yet fully exploited and further developments are needed, as will be presented in this contribution.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main methods for extracting cracks from 3D point clouds. (1) projecting dense 3D point clouds into 2D images and extracting cracks using image-processing techniques [ 21 , 22 ]; and (2) extracting cracks directly from the 3D point clouds [ 23 , 24 ]. Based on the first method, Yang et al [ 25 ] used the reflectance information from point clouds to detect cracks in a tunnel structure through morphology and a Canny edge detection operator, but there were many fractures in the detected cracks.…”
Section: Introductionmentioning
confidence: 99%